THE ANTI- CANCER SYNERGISTIC EFFECT OF COLCHICINE AND ON CANCER CELLS PROLIFERATION (IN VITRO STUDY) CHOLOROQUINE - Sumaia Samir Bakir Sidqiy; Waseem Ali Hasan; Firas Subhi Salah (Scholar Express Journals, 2022)
This study aimed to investigate the possible in vitro cytotoxicity of Colchicine and Chloroquine.
Keywords: study; cytotoxicity; Colchicine